Estimation De La Croissance De La Sardine (Sardina Pilchardus Walb, 1792) De La Rgion Centre Et Est De La Mditerrane Marocaine A Laaide De Latude Des Otolithes (Global Journal of Science Frontier Research, 2013)
The study of the growth of the sardine Sardina pilchardus which populates the Moroccan Mediterranean coasts, based on the direct reading of the otoliths extracted from the internal ear, has allowed us to evaluate the age of 1015 specimens. The latter were sampled from the unloadings carried out in the main ports of the Moroccan Mediterranean from 2002 to 2004. The parameters of growth based on the equation of Von Bertalanffy are: L∞ = 21.3 cm, k =0.56, to= – 0.67, W∞= 76.2 ; a= 0,0066 and b= 3.0582.
Keywords: Moroccan Mediterranean parameters of growth based